Discrimination and genetic diversity of Wheat dwarf virus in the Czech Republic - Kundu, J K; Gadiou, S; Cervená, G (Virus genes, 2009)
Cereal-infecting Mastreviruses are one of the most ubiquitous of viruses, having caused huge yield losses during the last decade in the Czech Republic. The presence of two strains of Wheat dwarf virus (WDV), one of which is wheat adapted and one barley adapted, have been confirmed from among field samples of wheat and barley plants. The virus typing was conducted by both PCR-RFLP and sequencing-based methods. The Czech WDV isolates of the barley strain are more variable than the isolates of the wheat strain, separating them into two clades, one representing a pool of divergent isolates. The RFLP analysis confirmed the separation of the Czech isolates into two strains and highlights a powerful method for the rapid diagnosis of both the wheat and barley strains. Additionally, both RFLP and sequence analysis have shown that the barley strain is restricted to the barley host, while the wheat strain is present in both wheat and barley plants.
Keywords: ječmen (rod); Triticum; nemoci rostlin; Genotype; polymorfismus délky restrikčních fragmentů; DNA Fingerprinting; DNA, Viral; shluková analýza; Molecular Sequence Data; genotyp; DNA fingerprinting; Genetic Variation; Phylogeny; Polymorphism, Restriction Fragment Length; Geminiviridae; molekulární sekvence - údaje; Czech Republic; Plant Diseases; Sequence Analysis, DNA; Česká republika; Hordeum; sekvenční analýza DNA; pšenice; Cluster Analysis; fylogeneze; genetická variace; DNA virů